Magnetoreception—A sense without a receptor - Nordmann, Gregory C.; Hochstoeger, Tobias; Keays, David A. (PLOS Biology, 2017)
Evolution has equipped life on our planet with an array of extraordinary senses, but perhaps the least understood is magnetoreception. Despite compelling behavioral evidence that this sense exists, the cells, molecules, and mechanisms that mediate sensory transduction remain unknown. So how could animals detect magnetic fields? We introduce and discuss 3 concepts that attempt to address this question: (1) a mechanically sensitive magnetite-based magnetoreceptor, (2) a light-sensitive chemical-based mechanism, and (3) electromagnetic induction within accessory structures. In discussing the merits and issues with each of these ideas, we draw on existing precepts in sensory biology. We argue that solving this scientific mystery will require the development of new genetic tools in magnetosensitive species, coupled with an interdisciplinary approach that bridges physics, behavior, anatomy, physiology, molecular biology, and genetics.